Digital comic learning media based on character values on students’ critical thinking in solving mathematical problems in terms of learning styles - Darmayanti, Rani; Sugianto, Rahmad; Baiduri, Baiduri; Choirudin, Choirudin; Wawan, Wawan (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
To prepare students to compete in 21st-century skills, the Ministry of Education and Culture of the Republic of Indonesia integrates character education into school subjects. However, as a medium, comics do not contain the level of character values, exploration, and critical thinking skills in problem-solving on geometry material. Therefore, the aim of this study is to produce digital media based on character values on mathematical critical thinking skills in solving problems related to learning styles for eighth-grade students. This development research employed the 4-D method (Define, Design, Develop, and Disseminate). The study indicates that the digital comic learning media is valid with a total average score of 3.60 based on the material expert’s validation and 3.50 based on the media expert’s validation. The eight-grade students' responses were positive (92%) based on the trials. The learning outcomes in terms of kinesthetic, auditory, and visual learning styles used in this study can all meet all indicators of mathematical problem-solving.